SOFT SKILLS FOR TEACHERS: ACCEPTING STANDARD GURU MALAYSIA 2.0 (SGM) AND SSB4K THEORY IN FUTURE TEACHING PRACTICES - Fahainis Mohd. Yusof; Fuziah Shaffie; Ruzlan Md-Ali , (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This paper discusses how Kemahiran Insaniah (KI) (softs kills) for teachers are constructed by accepting the combination of the Standard Guru Malaysia (SGM) 2.0 and Sistem Sahsiah Bersepadu 4K (SSB4K) or Integrated Personality System Theory. The main objective of the study was to highlight the contents of the SGM2.0 and SSB4K in order to propose teachers with relevant soft skills for transition into various education landscapes. The realisation of this objective can be met if most of the qualities of the features drawn from the SGM 2.0 together with SSB4K offer relevant and responsive curricula in line with current teaching practices. In this article, the researchers address the concern of experts’ views on the way experts see themselves as professionals teaching and how they compose their identities. Three data themes, expert authority, commitment to the profession, and multitasking are theorised from a symbolic interactionist (SI) framework, using constructs such as situational, social, and personal identity. This study is part of a larger research project involving the development of the understanding of the soft skills of teachers and broader teacher standards issues within Malaysian context. This study aimed to outline the current soft skills of teachers. The data were analyzed by qualitative content analysis. Two kinds of perspectives are described: the media perspective by illustrating what kind of descriptions, evaluations, and requirements of SGM2.0 and SSB4K is established in framing soft skills for teachers and the experts’ perspective by reporting the experiences and evaluations of themselves. These two perspectives are described and interpreted. The findings show that soft skills are a crucial part of the competence of teachers. Four main categories of soft skill competencies were oral communication skills, media digital skills, thinking skills, and leadership skills.